Unfettering Poetry - Robinson, J. author. aut Link
X, 301 p.
Keywords: This book calls attention to the pervasive but largely unacknowledged poetics of the 'Fancy' evident in poetry written during the British Romantic period. These poetics, Robinson demonstrates, are an early nineteenth-century version of what will become the visionary, experimental, open-form poetics of the twentieth-century.